Nursing care using KT (Kuchi-kara Taberu) index radar chart enabling elderly patients with dysphagia to live like human beings after initiating gastrostomy feeding. (June 2018) - Aruga, Yumiko; Saito, Ayako; Aoki, Yuji
Some patients with severe dysphagia need to undergo percutaneous endoscopic gastrostomy (gastrostomy feeding), which improves nutrition but leads them to feel they are not living like human beings. The KT (Kuchi-kara Taberu, or ingesting orally in Japanese) index was developed in order to comprehensively assess and intervene in problems with eating and swallowing. We present three cases where the KT index improved quality of life after gastrostomy feeding. Through continued nursing care using the KT index, the patient in Case 1 was able to eat orally again; the patient in Case 2 could eat a piece of jelly and communicate a little; and the patient in Case 3 was able to ingest a small amount of food orally, with support from her husband. Thus, the feeding support provided by the KT index radar chart improves quality of life, even after the implementation of gastrostomy feeding. Further studies are needed to investigate how the KT index best helps elderly patients with severe dysphagia live like human beings while taking into account the perspectives of patients and their family members.